SEJARAH MARGINALISASI ORANG RIMBA BUKIT DUA BELAS DI ERA ORDE BARU - Muchlis, Fuad; Lubis, Djuara P.; Kinseng, Rilus A.; Tasman, Aulia (History Department, Semarang State University and Historian Society of Indonesia, 2016)
The dynamics life of Orang Rimba at Bukit Dua Belas National Park is inseparable from the forest, because the forest become the foundation of the survival of the Orang Rimba and to be identifies the various wisdom traditions and culture of Orang Rimba. Problems then arise when the forest as a living space of Orang Rimba being massively exploited. This article describes the a portrait of the life and history of the Orang Rimba and marginalization of Orang Rimba at TNBD. Results of the study explained that the historical changes in cultural identity and lifestyle Orang Rimba is not regardless of changes in the landscape that is constantly degraded TNBD. The degradation as a result of state policy by granting permission HPH, HTI and oil palm plantations and transmigration program was a major factor in the marginalization of Orang RimbaÂ Dinamika kehidupan Orang Rimba di Bukit Dua Belas tidak terlepas dari hutan,Â karena hutan menjadi tumpuan keberlangsungan hidup Orang Rimba dan menjadi identitas berbagai kearifan, tradisi dan budaya Orang Rimba. Persoalan muncul saat hutan sebagai ruang kehidupan mereka terus menerus tereksploitasi secara massif. Artikel ini mendeskripsikan potret kehidupan Orang Rimba dan sejarah marginalisasi terhadap Orang Rimba Bukit Dua Belas di Era Orde Baru. Hasil penelitian menjelaskan bahwa perubahan identitas budaya dan pola hidup Orang Rimba tidak terlepas dari perubahan bentang alam di Bukit Dua Belas terus terdegradasi. Degradasi akibat kebijakan negara melalui pemberian izin HPH, HTI dan perkebunan kelapa sawit serta program transmigrasi menjadi faktor utama marginalisasi Orang Rimba.Â